The effect of the project-based learning model on students' mathematics problem-solving abilities - Lisa Dwi Afri; Eka Khairani Hasibuan; Putri Anggi Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
This research aims to investigate the impact of the project-based learning model on students' problem-solving abilities. The study employed a quantitative research methodology with a quasi-experimental design. Specifically, a pretest-posttest control group approach was used. The population under investigation consisted of all students in the Mathematics Education study program at the Faculty of Tarbiyah and Teacher Training (FITK), UIN North Sumatra Medan. The sampling technique employed cluster random sampling, resulting in 26 students from the PMM-2 class being selected as the experimental group, while 27 students from the PMM-1 class served as the control group. Data collection involved a problem-solving ability test in descriptive form. For hypothesis testing, the independent sample t-test was utilized, preceded by tests to assess normality and homogeneity. The analysis of post-test data revealed a significance value of 0.0000 <